A tea exosome-integrated self‑oxygenating cascade chitosan/oxidized alginate hydrogel for remodeling the hyperglycemic and hypoxic microenvironment in diabetic wound healing - Li-Hua Xie; Xin-Hui Zhou; Wei-Qiu Wen; Wei Wang; Ping Gui; Li Li; Guan-Hai Wang (Carbohydrate Polymers, 2026)

Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

Bicarbonate-driven enhancement of PGPR-assisted phytoremediation for Cu-contaminated soil through plant-microbiome interactions - Ping Wang; Yixuan Lü; Wenxuan Li; Yang Zhao; Zhiman Li; Xingke Yang; Yuankai Yang; Huijun Guan; Yixin Feng; Lixue Zheng; Ke Chen; Tianlong Hao; et al. (Rhizosphere, 2026)

Rare earth elements as emerging contaminants: Multi-source release, geochemical tracing, and implications for environmental monitoring and management - Yong-He Han; Ming-Zhu Zou; Dong-Xing Guan; Yi-Xi Li; Ping Xiang; Yong Zhang; Hong Zhang; Zhibiao Chen (Journal of Environmental Management, 2026)

Functionalized biochar loaded with plant growth-promoting Enterobacter sp. TK: A bifunctional material for cadmium immobilization and maize-assisted phytoremediation - Xingke Yang; Wenxuan Li; Yuankai Yang; Yixuan Lü; Yang Zhao; Ke Chen; Lixue Zheng; Huijun Guan; Yixin Feng; Ping Wang; Tianlong Hao; Chunfeng Guan (Chemical Engineering Journal, 2026)

Bioactive prenylated acylphloroglucinols from Hypericum scabrum - Li-Ping Teng; Jie-Lian Huang; Shui-Qing Guan; Chen-Xi Xin; Zi-Yin Mai; Yik-Ling Chew; Zhong-Bo Zhou; Gencheng Liang (Natural Product Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Carbohydrate conversion and microbial community restructuring following Saccharomyces cerevisiae inoculation during Pu-erh tea fermentation - Ruoyu Li; Teng Wang; Qiuyue Chen; Yanhui Guan; Nianguo Bo; Qi Wang; Yiqing Guan; Dihan Yang; Ping Liang; Yan Ma; Tiejun Ling; Ming Zhao (International Journal of Food Microbiology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Ganoderma lucidum spore lipid extract synergizes with chemotherapy to alleviate tumor progression by enhancing macrophage phagocytosis of dying tumor cells - Guan-Di Xiao; Zi-Xuan Li; Yi-Fang Li; Lei Liang; Cheng Yuan; Wen-Dong Xu; Ju-Yan Liu; Yan-Ping Wu; Rong-Rong He (PharmaNutrition, 2026)

Sediment physicochemical and dissolved organic matter control microbial responses and nitrous oxide emissions across a coastal wetland transition from invasion to reclamation - Shengwei Cao; Yaci Liu; Ping Yang; Xiujian Hu; Yan Dong; Xiangyu Guan; Ping Yin; Yasong Li (Journal of Environmental Management, 2026)

Different land use types around megacities contribute contrasting heavy metal pollution and health risks in soil-leaf vegetable systems - Ling Huang; Wen-Fei Chen; Yue-E Guan; Yan-Ping Pang; Sheng-Gong Yu; Lin Li; Qi Zou; Meng-Qiang Sun; Hang Wei; Zhi-Liang Chen (Environmental Research, 2026)

Competition partially decouples the climate-growth relationship in plantations and reduces their drought resilience - Chongfan Guan; Jinsong Zhang; Shoujia Sun; Wanting Gao; Zijing Li; Jinfeng Cai; Ping Meng (Agricultural and Forest Meteorology, 2026)

Synergistic promotion of diabetic wound healing by glucose-responsive functional chitosan-based composite nanohydrogels - Runze Yang; Jiale Sun; Guanglan Peng; Mingcai Wu; Chengen Guan; Jianping Yang; Zeyuan Wang; Wanzhen Li; Longbao Zhu; Jun Wang; Zuchun Zhao; WeiWei Zhang; et al. (Carbohydrate Polymers, 2026)

Marine biomaterials for advanced food packaging: From sourcing to intelligent functional design and commercial prospects - Cheng Wang; Mengru Zhang; Tong Zhang; Haitao Du; Hongmin Xia; Renwei Guan; Fengdan Guo; Xinyi Li; Mingming Wang; Xiuwen Jia; Ping Wang (Trends in Food Science & Technology, 2026)

An innovative triple-channel probing strategy for ultrasensitive detection of quercetin in food matrices based on carbon dots - Ping Li; Zhen-quan Yang; Lixia Xiao; Xuechao Xu; Tianzu Guan; Wenyuan Zhou; Xiaowei Tang; Xiaojuan Gong; Qin Hu (Food Chemistry, 2026)

Enhanced Chaetoceros muelleri growth using optimized fermented agricultural waste - Yong Feng; Keyi Li; Yutong Xia; Ping Wu; Zhen Wang; Shuhao Huo; Guoqiang Guan; Huayou Chen (Systems Microbiology and Biomanufacturing, 2026)

The emerging role of fatty acids as key bioactive components of Ganoderma lucidum spore oil in alleviating tumor progression - Qi-Jun Chen; Zi-Xuan Li; Guo-Cai Wang; Ting Xie; Guan-Di Xiao; Hui Xu; Jing Li; Xiang Luo; Yi-Fang Li; Lei Liang; Ju-Yan Liu; Yan-Ping Wu; et al. (Journal of Natural Medicines, 2026)

Three new matrine-type alkaloids from Sophora alopecuroides with cytotoxic activity - Yan-Ping Qiu; He Tian; Qian Xie; Shuai Li; Bi-Qian Dong; Guan-Min Su; Ding Luo; Lin-Zhao Ye (Phytochemistry Letters, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

Partial consistency of net primary productivity and water-carbon use efficiency in response to climate change among three plantations - Chongfan Guan; ShouJia Sun; Jinsong Zhang; Xiaochuang Hu; Zijing Li; Jinfeng Cai; Ping Meng (Ecological Modelling, 2026)

Anti-epileptic effect of saikosaponin a by inhibiting ferroptosis via the IL-17/Akt/ERK signaling pathway in the temporal lobe epilepsy model - Ping-Ping Li; Wen-Wen Wang; Jing-Tao Wang; Zi-Ao Xu; Xue-Fei Ji; Liao Guan; Lei Ye; Hong-Wei Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

3D reconstruction of the ovariole in Nilaparvata lugens (Hemiptera: Delphacidae) by FIB-SEM - Ke-Qi Ye; Guan Wang; Jian-Sheng Guo; Chuan-Xi Zhang; Xiao-Ping Yu; Dan-Ting Li (Cell and Tissue Research, 2025)

Corrigendum to ‘Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A’ [Phytochemistry. 222 (2024) 114073] - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li Ping Lin (Phytochemistry, 2025)

Driving mechanism of iron cycling towards energy recovery and pollutant removal in constructed wetland-microbial fuel cell - Rongdi An; Nan Lu; Hanyu Ju; Zhuoyu Li; Xiamu Zelang; Ping Lu; Lianxi Sheng; Hongfeng Bian; Jiunian Guan (Journal of Environmental Chemical Engineering, 2025)

Activity and sulfur resistance enhancement of metal-based catalysts derived from layered double hydroxides for selective catalytic reduction of NO with NH3 - Gan Chen; Zhenzhen Guan; Shifeng Zhou; Yu Guo; Ziying Yang; Jiang Wu; Fangqin Li; Ping He; Xinxia Ma (Fuel, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Incorporating atomic-level center into porphyrin-based COF for photocatalytic H2 evolution - Guo-Wei Guan; Su-Tao Zheng; Li-Ping Zhang; Si-Yu Hou; Xiang-Yu Liu; Qing-Yuan Yang (Chemical Engineering Journal, 2025)

Five undescribed chromone-phenylpyridone hybrids from Cineraria repanda-derived Penicillium oxalicum with cytotoxic and antibacterial activity - Yu Wei Huang; Jing Guan; Yin Tang; Ren Xiang Tan; Li Ping Lin (Phytochemistry, 2025)

Restoring turbid eutrophic shallow lakes to a clear-water state by combined biomanipulation and chemical treatment: A 4-hectare in-situ experiment in subtropical China - Bo Li; Deyuan Chen; Jichong Lu; Suxia Liu; Jiale Wu; Lei Gan; Xiaoqin Yang; Xiaolin He; Hu He; Jinlei Yu; Ping Zhong; Yali Tang; et al. (Journal of Environmental Management, 2025)

Deciphering denitrification drivers in a high‑nitrogen estuary: Insights from stable isotope analysis and microbial molecular techniques - Shengwei Cao; Ping Yin; Chunlei Liu; Xiujian Hu; Yaci Liu; Yuewen Zhao; Xiangyu Guan; Yasong Li (Science of The Total Environment, 2025)

Rapid and accurate identification of Panax ginseng origins based on data fusion of near-infrared and laser-induced breakdown spectroscopy - Jiacong Ping; Nan Hao; Xuting Guo; Peiqi Miao; Zhiqi Guan; Haiyang Chen; Changqing Liu; Gang Bai; Wenlong Li (Food Research International, 2025)

Low-temperature regulated interfacial polymerization of nanofiltration membrane for efficient Li+/Mg2+ separation - Shaofan Duan; Shuai Jiang; Zhan Li; Pengfei Zhang; Kecheng Guan; Ping Xu; Hideto Matsuyama (Desalination, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Megastigmane glycoside and phenol glycosides from the bark of Mallotus barbatus - Chenyang Ren; Ping Hou; Jian Li; Yan Huang; Liwei Pan; Liuting Peng; Chunqiu Gan; Xinlan Guan; Jun Li (Natural Product Research, 2025)

Functionalization of waste-derived artificial aggregates: A state-of-the-art review - Lan-Ping Qian; Ling-Yu Xu; Bo-Tao Huang; Yi Li; Jirong Lan; Fuyuan Gong; Hong Guan (Resources, Conservation and Recycling, 2025)

Multifunctional role of surfactant in fabricating polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Aiwen Zhang; Liheng Dai; Siyu Zhou; Wenming Fu; Mengyang Hu; Ping Xu; Pengfei Zhang; Zhan Li; Zhaohuan Mai; Hideto Matsuyama (Desalination, 2025)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

Polyethylenimine-assisted preparation of Zr-MOF/GO membranes for radionuclide separation - Chuang Li; Zhan Li; Kecheng Guan; Yu-Hsuan Chiao; Pengfei Zhang; Ping Xu; Ralph Rolly Gonzales; Mengyang Hu; Zhaohuan Mai; Tomohisa Yoshioka; Hideto Matsuyama (Desalination, 2024)

Evolution and legacy of East Asian aurochs - Jiawen Hou; Xiwen Guan; Xiaoting Xia; Yang Lyu; Xin Liu; Yuri Mazei; Ping Xie; Fengqin Chang; Xiaonan Zhang; Jialei Chen; Xinyi Li; Fengwei Zhang; et al. (Science Bulletin, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Characteristics and assembly mechanisms of bacterial and fungal communities in soils from Chinese forests across different climatic zones - Ming Sheng; Wei Hu; Cong-Qiang Liu; Mutong Niu; Rui Jin; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (CATENA, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Ionomer distribution control for improving the performance of proton exchange membrane fuel cells: Insights into structure–property relationships - Jingnan Song; Wutong Zhao; Haibo Wang; Hongjie Meng; Shukai Zhang; Wenkai Zhong; Xuefei Wu; Min Li; Panpan Guan; Ming Zhang; Lei Zhu; Ping He; et al. (Chemical Engineering Journal, 2024)

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Hydrogel membrane composite reduces fouling and retains ammonium efficiently - Ralph Rolly Gonzales; Jing Li; Pengfei Zhang; Ping Xu; Zhan Li; Mengyang Hu; Zhaohuan Mai; Kecheng Guan; Hideto Matsuyama (Environmental Chemistry Letters, 2024)
The recovery of pure water and valuable substances from wastewater is a major challenge in the context of the circular economy, requiring advanced separation methods. However, actual membrane separation techniques such as forward osmosis are limited by membrane fouling and selectivity. Here, we synthesized composite membranes by crosslinking polyvinyl alcohol hydrogel, using both glutaraldehyde and borax as crosslinking agents, on top of cellulose ester membranes. We tested these composite membranes on model and real wastewater. Results show that the composite membranes retain ammonium effectively, maintain surface electroneutrality, and exhibit remarkable resistance to fouling by organic and biological contaminants. This is explained by the high hydrophilicity of the membrane surface after application of a hydrogel layer.

Ternary-coordination-regulated polyamide nanofiltration membranes for Li+/Mg2+ separation - Shang Fang; Kecheng Guan; Siyu Zhou; Qiangqiang Song; Yongxuan Shi; Wenming Fu; Zhan Li; Ping Xu; Mengyang Hu; Zhaohuan Mai; Pengfei Zhang; Hideto Matsuyama (Desalination, 2024)

Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li-Ping Lin (Phytochemistry, 2024)

Ferulic acid alleviates avermectin induced renal injury in carp by inhibiting inflammation, oxidative stress and apoptosis - Qiulu Li; Kaixin Ping; Yannan Xiang; Ying Sun; Zunhan Hu; Shujuan Liu; Xinying Guan; Mian Fu (Fish & Shellfish Immunology, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Core-shell DOPO/caramel nano-polymer with desirable UV shielding and flame retardancy for polyamide 6 fabric - Wen-Jie Jin; Xian-Wei Cheng; Sheng-Nan Ma; Ling Li; Rui-Kai Wu; Jin-Ping Guan (Chemical Engineering Journal, 2024)

Nickel phosphide cocatalyst and carbon defects simultaneously boosting the photocatalytic hydrogen production over carbon nitride - ChuChang Mao; Qinghua Qu; Fada Li; Cheng Fang; Hongping Li; Jing Ding; Hui Wan; Ping Zhang; Guofeng Guan (Journal of Environmental Chemical Engineering, 2024)

Silybin mitigates chronic Avermectin exposure-induced intestinal damage and growth inhibition in carp - Guanglu Wang; Yue Xin; Kaixin Ping; Xuhui Xu; Ying Sun; Xing Li; Xinying Guan; Jingquan Dong (Environmental Toxicology and Pharmacology, 2024)

Mechanisms of Ferritinophagy and Ferroptosis in Diseases - Siqi Li; Ping Huang; Feifan Lai; Ting Zhang; Jiaqi Guan; Haitong Wan; Yu He (Molecular Neurobiology, 2024)

Promoting effect of Cu and Mn doping on the Fe/ZSM-5 catalyst for selective catalytic reduction of NO with NH3 - Yuheng Qiao; Zhenzhen Guan; Mengyan Zhang; Gan Chen; Shifeng Zhou; Hailong Liu; Jiang Wu; Ruitang Guo; Weiguo Pan; Fangqin Li; Ping He (Fuel, 2024)

Investigation on the failure mechanism of a tunnel entrance high-steep slope with ultra-large wedge blocks based on discrete element method - Huai-sheng Xu; Shao-jun Li; Ding-ping Xu; Xiu-yang Liu; Yue-lin Xia; Guan-qi Wang; Xing-dong Ma; Zheng-jun Zhou (Computers and Geotechnics, 2024)

Fluorogenic RNA aptamer output sensors via transcription activated by recombinase polymerase amplification for nucleic acid testing - Jiajie Liang; Xin Liu; Wei Xiao; Peijun Teng; Ping Guan; Wanli Liang; Liangshan Hu; Guanbo He; Haorong He; Gan Li; Siyi Zou; Cheng Lu; et al. (Chemical Engineering Journal, 2024)

Removal and recovery of phosphate by modified oyster shell and its fertilizer application - Ping Li; Jianxu Li; Weirui Chen; Xiujuan Guan; Bing Tang; Liying Bin; Shaosong Huang (Science of The Total Environment, 2024)

Accumulation of livestock manure–derived heavy metals in the Hexi Corridor oasis agricultural alkaline soil and bioavailability to Chinese cabbage (Brassica pekinensis L.) after 4-year continuous application - Tian-Xia Guan; Zhao-Ping Lu; Ming Yue; Bao-Guo Li; Ai-Gen Fu; Xu-Dong Zhang; Zhong-Hu Li (Environmental Pollution, 2024)

Precipitation regulated soil nematode community and footprint in cropland ecosystems - Pingting Guan; Jianan Li; Cao Hao; Jingjing Yang; Lihong Song; Ximei Niu; Ping Wang; Mohammad Mahamood; Donghui Wu (Soil Ecology Letters, 2023)

Cytotoxic phenyl polyketides from Hypericum curvisepalum N. Robson - Qiu-Ying He; Hong Zeng; Qiu-Lan Zhang; Guan-Fang Qin; He-Bin Wang; Li-Ping Teng; Zhong-Bo Zhou (Natural Product Research, 2023)

Improvement of anti-wetting and anti-scaling properties in membrane distillation process by a facile fluorine coating method - Zhan Li; Pengfei Zhang; Yu-Hsuan Chiao; Kecheng Guan; Ralph Rolly Gonzales; Ping Xu; Zhaohuan Mai; Guorong Xu; Mengyang Hu; Tooru Kitagawa; Tomohisa Yoshioka; Hideto Matsuyama (Desalination, 2023)

Spatial and molecular variations in forest topsoil dissolved organic matter as revealed by FT-ICR mass spectrometry - Ming Sheng; Shuang Chen; Cong-Qiang Liu; Qinglong Fu; Donghuan Zhang; Wei Hu; Junjun Deng; Libin Wu; Ping Li; Zhifeng Yan; Yong-Guan Zhu; Pingqing Fu (Science of The Total Environment, 2023)

Near-infrared-triggered chirality-dependent photodynamic therapy based on hybrid upconversion nanoparticle hydrogels - Tianyong Guan; Yan Liu; Jiayao Li; Mingmao Chen; Xiaoying Shang; Ping Hu; Renfu Li; Hang Gao; Datao Tu; Wei Zheng; Xueyuan Chen (Chemical Engineering Journal, 2023)

Detection of citrus pests in double backbone network based on single shot multibox detector - Jun Qiang; Wuji Liu; Xixi Li; Ping Guan; Yunlong Du; Ben Liu; Guanglei Xiao (Computers and Electronics in Agriculture, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Ultra-low concentration terbium (Tb) adsorption on garlic peels biosorbent and its application for Nd-Fe-B scraps recovery - Qingqing Chang; Ping Li; Yunwu Han; Xindi Guan; Jiachun Xiong; Qian Li; Hailin Zhang; Kai Huang; Xin Zhang; Haijiao Xie; Tao Qi (Journal of Environmental Chemical Engineering, 2023)

Effect of Levilactobacillus brevis as a starter on the flavor quality of radish paocai - Xiru Zhang; Yaxin Li; Yaran Zhao; Hui Guan; Chengwu Jin; Hansheng Gong; Xuemei Sun; Ping Wang; Huamin Li; Wenli Liu (Food Research International, 2023)

Confined and mediated intercalation of nanoparticles in graphene oxide membrane to fine-tune desalination performance - Siyu Zhou; Kecheng Guan; Zheng Wang; Qiangqiang Song; Zhan Li; Ping Xu; Luyao Deng; Shang Xiang; Hideto Matsuyama (Chemical Engineering Journal, 2023)

A new procedure for separating thallium from geological materials prior to stable isotope ratio determination by MC–ICP–MS - Zhao-Yang Wang; Jie Li; Lu Yin; Le Zhang; Jun-Jie Liu; Neng-Ping Shen; Shuang Yan; Qing-Dian Guan (Chemical Geology, 2023)

Interactions between Cr(VI) and the hydrochar: The electron transfer routes, adsorption mechanisms, and the accelerating effects of wood vinegar - Zirui Wang; Nan Lu; Xu Cao; Qingzi Li; Shangyu Gong; Ping Lu; Ke Zhu; Jiunian Guan; Til Feike (Science of The Total Environment, 2023)

Effect of thermal treatment on the flavor quality of Chinese spicy cabbage - Xiru Zhang; Hui Guan; Qiang Zhao; Hansheng Gong; Dacheng Wang; Ping Wang; Huamin Li; Wenli Liu (Food Control, 2023)

Phospholipase A2 induces acute kidney injury by complement mediated mitochondrial apoptosis via TNF-α/NF-κB signaling pathway - Xin Tang; Tiantian Wei; Mingjing Guan; Peiyun Li; Yajun Pu; Lixin Cheng; Zhifeng Zhou; Ping Fu; Ling Zhang (Food and Chemical Toxicology, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

Salinimicrobium sediminilitoris sp. nov., Isolated from a Tidal Flat - Cheng-Qiang Xia; Hui-Jing Niu; Kai-Shi Dong; Li Guan; Li-Ping Sun; Qin Wang; Yan-Jiao Zhang; Yi Li; Cai-Xia Pei (Current Microbiology, 2022)

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

Four new secoiridoids from the stem barks of Syringa reticulata (Bl.) Hara - Shuang Guo; Yan Liu; Yan-Ping Sun; Juan Pan; Wei Guan; Xiao-Mao Li; Si-Yi Wang; Adnan Mohammed Algradi; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Two new terpenes from the aerial parts of Clematis chinensis Osbeck - Sun Ye; Liu Yan; Yan-Ping Sun; Xiao-Mao Li; Wang Si-Yi; Juan Pan; Wei Guan; Yuan Liu; Anam Naseem; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Four new polyacetylenes from the roots of Saposhnikovia divaricata - Yan Sun; Yan-Ping Sun; Yan Liu; Juan Pan; Wei Guan; Xiao-Mao Li; Yuan Liu; Anam Naseem; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Genomic characterization of a new enamovirus infecting common bean - Ruo-bin Lu; Ping-xiu Lan; Ru-jing Kang; Guan-lin Tan; Xiao-jiao Chen; Ruhui Li; Fan Li (Archives of Virology, 2022)

Seven new glycosides from the leaves of Datura metel L. - Jin-Yan Tan; Yan Liu; Yan-Gang Cheng; Yan-Ping Sun; Xiao-Mao Li; Wei Guan; Juan Pan; Bing-You Yang; Hai-Xue Kuang (Natural Product Research, 2022)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

Design, synthesis, and antidepressant/anticonvulsant activities of 3H-benzo[f]chromen chalcone derivatives - Qiu-Wan Tan; Li-Ya He; Zhi-Wen He; Wei-Hua Liu; Shan-Shan Zhang; Lin Lin; Hong-Li Yang; Li-Ping Guan (Medicinal Chemistry Research, 2021)

First report of Bacillus altitudinis causing seed rot of pomegranate in China - Qili Liu; Dongxiao Li; Haiyan Hu; Qianqian Huang; Yongheng Zhang; Feng Zhou; Puwen Song; Yuanyuan Guan; Ruifang Bu; Ping Hu; Jianjun Hao; Chengwei Li (Australasian Plant Pathology, 2021)

Effects of Tobacco Stem-Derived Biochar on Soil Properties and Bacterial Community Structure under Continuous Cropping of Bletilla striata - Linyan Zhao; Huilin Guan; Rui Wang; Haoji Wang; Zecheng Li; Wei Li; Ping Xiang; Wumei Xu (Journal of Soil Science and Plant Nutrition, 2021)

Nutrigenomics reveals potential genetic underpinning of diverse taste preference of Chinese men - Zhouhai Zhu; Junpu Mei; Silong Sun; Sheming Lu; Meng Li; Ying Guan; Ying Chen; Yuqiong Xu; Tao Zhang; Fengxue Shi; Xuemei Li; Mingming Miao; et al. (Genes & Genomics, 2021)

Synthesis and biological effects of naphthalene-chalcone derivatives - Qing-Hao Jin; Hong-Hai Chen; Wen-Bo Chen; Zhi-Yang Fu; Li-Ping Guan; Hai-Ying Jiang (Medicinal Chemistry Research, 2020)

The loess landslide on 15 march 2019 in Shanxi Province, China - Wenhui Shi; Yanrong Li; Weiwei Zhang; Jin Liu; Shengdi He; Ping Mo; Fanfan Guan (Landslides, 2020)
On 15 March 2019, a fatal deep-seated landslide occurred at the village of Zaoling in Xiangning County of Shanxi Province, China. Extending to an area of about 120 m by 85 m, with an estimated displaced mass volume of 72,000 m 3 , the landslide left 20 people dead, 13 injured, and 8 buildings destroyed. There were no precursory signals prior to the event, and usual triggering mechanisms for a landslide were absent. Investigation conducted immediately after the incident revealed that the landslide was initiated in a 1.0 to 1.5-m thick-softened layer located at 40 m depth along the contact between the loess and interbedded paleosol layer. This softened layer was highly saturated due to the perched water on top of the relatively impervious paleosol layer and became a critical weak zone since the shear strength of loess is very sensitive to water content. We suggest that the perched water originated from extensive long-term unsaturated seepage of rainwater and local rapid percolation along preferential channels such as sinkholes and root network. The Zaoling landslide confirms that unlike most landslides in non-loess areas, loess landslides can occur without identifiable triggering events. They can result from gradual build up of instability due to slow (in the span of hundred years) accumulation of deep soil water. Based on the lessons learned from this landslide event, suggestions are given for the planning of urban and rural development in loess areas. Due to the fact that the process leading to the development of such a landslide is largely concealed, further research should be aimed at gaining a more thorough understanding of the mechanism of this landslide type.

Nocardia panacis sp. nov., a novel actinomycete with antiphytopathogen activity isolated from the rhizosphere of Panax notoginseng - Jia-Yun Hu; Lei Li; Guang Peng; Yi-Qing Li; Li-Hua Xu; Hui-Lin Guan; Li-Xing Zhao; Cui-Ping Miao (Antonie van Leeuwenhoek, 2020)

New anthraquinone and eurotinone analogue from the seeds of Senna obtusifolia and their inhibitory effects on human organic anion transporters 1 and 3 - Xu Pang; Li-Ming Wang; You-Cai Zhang; Li-Ping Kang; He-Shui Yu; Guan-Wei Fan; Li-Feng Han (Natural Product Research, 2019)

Expression of Ihh signaling pathway in condylar cartilage after bite-raising in adult rats - Hui-qing Long; Peng-fei Tian; Yu-xin Guan; Ling-xia Liu; Xiu-ping Wu; Bing Li (Journal of Molecular Histology, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

The Molecular Mechanisms of Protective Role of Se on the G0/G1 Phase Arrest Caused by AFB1 in Broiler’s Thymocytes - Ke Guan; Hang Li; Zhicai Zuo; Fengyuan Wang; Ping Hu; Xi Peng; Jing Fang; Hengmin Cui; Gang Shu; Ping Ouyang (Biological Trace Element Research, 2019)

Study on synthesis and biological effects of a series of 3,4-dihydroisoquinoline-2(1H)-carboxamide derivatives - Zhi-Yang Fu; Qing-Hao Jin; Ya-Nan Xia; Hai-Ying Jiang; Li-Ping Guan (Medicinal Chemistry Research, 2019)

The Protective Role of Selenium in AFB1-Induced Tissue Damage and Cell Cycle Arrest in Chicken’s Bursa of Fabricius - Ping Hu; Zhicai Zuo; Fengyuan Wang; Xi Peng; Ke Guan; Hang Li; Jing Fang; Hengmin Cui; Gang Su; Ping Ouyang; Yi Zhou (Biological Trace Element Research, 2018)

Climatology of tracked persistent maxima of 500-hPa geopotential height - Ping Liu; Yuejian Zhu; Qin Zhang; Jon Gottschalck; Minghua Zhang; Christopher Melhauser; Wei Li; Hong Guan; Xiaqiong Zhou; Dingchen Hou; Malaquias Peña; Guoxiong Wu; et al. (Climate Dynamics, 2018)

AMPK/NF-κB signaling pathway regulated by ghrelin participates in the regulation of HUVEC and THP1 Inflammation - Min Zhang; Shuping Wang; Zhicheng Pan; Tiantong Ou; Jianwei Ma; Hua Liu; Ruogu Li; Ping Yang; Wenzheng Han; Shaofeng Guan; Xumin Hou; Weiyi Fang; et al. (Molecular and Cellular Biochemistry, 2018)

Gracilibacillus aidingensis sp. nov., a novel moderately halophilic bacterium isolated from Aiding salt lake - Tong-Wei Guan; Lei Tian; En-Yuan Li; Shu-Kun Tang; Xiao-Ping Zhang (Archives of Microbiology, 2017)

Olivibacter flavus sp. nov., a novel endophytic bacterium isolated from the root of Camellia sinensis - Lei Tian; Tong-Wei Guan; Ling-Ling Yang; Kai-Yang Lu; Bing-Bing Liu; Wei-Xun ChunYu; Min Yin; En-Yuan Li; Yang Ji; Xiao-Ping Zhang; Shu-Kun Tang (Archives of Microbiology, 2017)

Reflection full-waveform inversion using a modified phase misfit function - Chao Cui; Jian-Ping Huang; Zhen-Chun Li; Wen-Yuan Liao; Zhe Guan (Applied Geophysics, 2017)

Antidepressant-like effects of saringosterol, a sterol from Sargassum fusiforme by performing in vivo behavioral tests - Hong-Guo Jin; Min Zhou; Qing-Hao Jin; Bing-Yu Liu; Li-Ping Guan (Medicinal Chemistry Research, 2017)

Dependency of UVR-induced photoinhibition on atomic ratio of N to P in the dinoflagellate Karenia mikimotoi - Wanchun Guan; Ping Li (Marine Biology, 2017)

Improvement of anti-nutritional effect resulting from β-glucanase specific expression in the parotid gland of transgenic pigs - Li-zeng Guan; Jin-shun Cai; Shuai Zhao; Yu-ping Sun; Jing-lan Wang; Yong Jiang; Gang Shu; Qing-yan Jiang; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2017)

Submerged macrophytes facilitate dominance of omnivorous fish in a subtropical shallow lake: implications for lake restoration - Jinlei Yu; Zhengwen Liu; Hu He; Wei Zhen; Baohua Guan; Feizhou Chen; Kuanyi Li; Ping Zhong; Franco Teixeira-de Mello; Erik Jeppesen (Hydrobiologia, 2016)

Inhibitory effect of Gardenblue blueberry (Vaccinium ashei Reade) anthocyanin extracts on lipopolysaccharide-stimulated inflammatory response in RAW 264.7 cells - Wei Xu; Qing Zhou; Yong Yao; Xing Li; Jiu-liang Zhang; Guan-hua Su; Ai-ping Deng (Journal of Zhejiang University-SCIENCE B, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Development and Psychometric Testing Chinese Version of the Frommelt Attitude Toward Care of the Dying Scale, Form B in Nurses and Nursing Students - Li-Ping Wang; Ya-Jie Li; Wen-Zhen Yan; Guan-Mei Li (Journal of Cancer Education, 2016)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

The aflatoxin-detoxifizyme specific expression in mouse parotid gland - Li-zeng Guan; Yu-ping Sun; Jin-shun Cai; Han-dong Wu; Long-zheng Yu; Yong-liang Zhang; Qian-yun Xi (Transgenic Research, 2015)

A Novel Oral Preparation of Hydroxysafflor Yellow A Base on a Chitosan Complex: A Strategy to Enhance the Oral Bioavailability - Guan-nan Ma; Fang-lin Yu; Shan Wang; Zhi-ping Li; Xiang-yang Xie; Xing-guo Mei (AAPS PharmSciTech, 2015)

Simulation of stable water isotopic composition in the atmosphere using an isotopic Atmospheric Water Balance Model - Xin‐Ping Zhang; Hua‐De Guan; Xin‐Zhu Zhang; Hua‐Wu Wu; Guang Li; Yi‐Min Huang (International Journal of Climatology, 2015)
In this article, we present a simplified isotopic Atmospheric Water Balance Model ( iAWBM ), to simulate spatial distribution and temporal variations of δ 18 O in atmospheric vapour and in precipitation, and the correlations of δ 18 O in precipitation with precipitation amount and with temperature. This method overcomes deficiencies of the Global Network of Isotopes in Precipitation ( GNIP ) due to its limitation in space and time resolution and those of the isotope‐enabled General Circulation Models ( iGCM s) due to its complexity. The simulated results reproduce well the latitude effect, continent effect and seasonality of δ 18 O in global precipitation. The simulation suggests that the precipitation amount effect occurs mainly in the low‐mid latitude oceans and monsoon areas, and the simulated temperature effect occurs mainly in the mid‐high latitude continents. However, the simulation results also indicate some temperature effect in some low‐latitude areas where the precipitation amount effect is strong. The modelled precipitation isotopic composition is compared to 3‐year observations in Changsha, China (2010–2012). The simulations reproduce the observed seasonal variations of δ 18 O in precipitation. The basic characteristics that stable isotopes in precipitation are depleted during the rainy season and enriched during the dry season, and the observed amount effect is well simulated under daily time scale. The simulated weighted average δ 18 O (−6.58‰) in precipitation during the prevailing winter monsoon season (October–March) is almost the same as the observed δ 18 O in the same period (−6.56‰), but the simulated δ 18 O (−9.58‰) during the prevailing summer monsoon season (April–September) is lower than the observed δ 18 O (−7.66‰). The simulation result also shows temporal variations of vapour isotopic composition in the atmosphere, and the proportional contributions from horizontal vapour exchange, precipitation and evaporation.

Genetic diversity and evolution of two capsid protein genes of citrus tristeza virus isolates from China - Guan-Wei Wu; Min Tang; Guo-Ping Wang; Feng-Yin Jin; Zuo-Kun Yang; Li-Jing Cheng; Ni Hong (Archives of Virology, 2015)

Effects of l-tryptophan-supplemented dietary on growth performance and 5-HT and GABA levels in juvenile Litopenaeus vannamei - Yu-Ping Sun; Li-Zeng Guan; Jie-Hua Xiong; Qian-Yun Xi; Yong-Liang Zhang (Aquaculture International, 2015)

Analysis of the ground settlement control of a large span metro station in Dalian city using the Centre Drift Method - Xin-Bo Ji; Wen Zhao; Shen-Gang Li; Yong-Wei Zhou; Yong-Ping Guan (European Journal of Environmental and Civil Engineering, 2014)

Structure-based design, synthesis, and anticonvulsant activity of isatin-1-N-phenylacetamide derivatives - Chao Xie; Li-Ming Tang; Fu-Nan Li; Li-Ping Guan; Cheng-Yan Pan; Si-Hong Wang (Medicinal Chemistry Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Bacillus thuringiensis subsp. sichuansis strain MC28 produces a novel crystal protein with activity against Culex quinquefasciatus larvae - Peng Guan; Xiaojuan Dai; Jun Zhu; Qiao Li; Shuangcheng Li; Shiquan Wang; Ping Li; Aiping Zheng (World Journal of Microbiology and Biotechnology, 2014)

Phylogeography of Hipposideros armiger (Chiroptera: Hipposideridae) in the Oriental Region: the contribution of multiple Pleistocene glacial refugia and intrinsic factors to contemporary population genetic structure - Ai‐Qing Lin; Gabor Csorba; Lin‐Feng Li; Ting‐Lei Jiang; Guan‐Jun Lu; Vu Dinh Thong; Pipat Soisook; Ke‐Ping Sun; Jiang Feng (Journal of Biogeography, 2014)
Aim The goals of our study were to assess the population history and genetic structure of the widespread bat H ipposideros armiger , and to evaluate the effect of palaeoclimatic changes and dispersal patterns on this species. Location S outh C hina, mainland S outheast A sia and the S outh H imalayas. Methods We amplified two mitochondrial DNA (mt DNA ) regions (cyt b and D ‐loop) and seven nuclear microsatellite loci (n SSR s) from 216 individuals of H . armiger . To examine the evolutionary history of this species, we constructed maximum likelihood and Bayesian phylogenetic trees based on the two mt DNA regions. From the mt DNA and/or n SSR data, we assessed population genetic structure using analysis of molecular variance ( AMOVA ) and median‐joining network and structure analyses. We also estimated demographic history and gene flow using a B ayesian skyline plot and the program I Ma 2. Results Phylogenetic and median‐joining network analyses revealed that H . armiger comprises two distinct mt DNA clades divided into seven subclades. The results of AMOVA suggested strong population genetic structure based on mt DNA , but weak structure based on n SSR s. structure analysis identified three population clusters and also showed weak genetic structure at the nuclear level. Demographic analyses revealed two population expansion events c . 0.62 Ma and c . 0.25 Ma. The basic phylogeographical structure of H . armiger was established by 0.24 Ma. I Ma 2 analysis demonstrated that substantial gene flow has occurred between different regions since then. Additionally, non‐significant population structure and significant gene flow were detected between T aiwan and H ainan island populations and those from mainland C hina. Main conclusions Our results suggest that divergence and population expansion of H . armiger occurred in association with P leistocene climatic changes and that multiple refugia may have existed for this species. Post‐glacial male‐biased dispersal was likely to be the primary contributor to the contemporary genetic structure of H . armiger populations. Gene flow may have contributed greatly to the genetic structure of insular populations and populations from mainland C hina.

Design, synthesis and antidepressant activity evaluation 2′-hydroxy-4′,6′-diisoprenyloxychalcone derivatives - Li-Ping Guan; Dong-Hai Zhao; Yue Chang; Yu Sun; Xiao-Li Ding; Jing-Fei Jiang (Medicinal Chemistry Research, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

Actinopolyspora dayingensis sp. nov., a novel halophilic actinomycete isolated from a hypersaline lake - Tong-Wei Guan; Hui-Ping Zhao; Zhen-Ming Che; Xiao-Ping Zhang; Li-Li Zhang (Antonie van Leeuwenhoek, 2013)

Factors underlying the association of body mass index with serum ALT in Chinese hypertensive adults without known hepatic diseases - Yan Zhang; Xian-hui Qin; Jian-ping Li; Yi-min Cui; Ze-yuan Liu; Zhi-gang Zhao; Jun-bo Ge; De-ming Guan; Jian Hu; Yan-ni Wang; Fu-min Zhang; Xin Xu; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

β-Glucanase specific expression in the parotid gland of transgenic mice - Li-zheng Guan; Yu-ping Sun; Qian-yun Xi; Jing-lan Wang; Jun-yun Zhou; Gang Shu; Qing-yan Jiang; Yong-liang Zhang (Transgenic Research, 2013)

Coastal Wetlands of China: Changes from the 1970s to 2007 Based on a New Wetland Classification System - Ping Zuo; Yun Li; Chang-An Liu; Shu-He Zhao; Dao-Ming Guan (Estuaries and Coasts, 2013)

Involvement of large conductance Ca2+-activated K+ channel in laminar shear stress-induced inhibition of vascular smooth muscle cell proliferation - Xiaoling Jia; Jingyun Yang; Wei Song; Ping Li; Xia Wang; Changdong Guan; Liu Yang; Yan Huang; Xianghui Gong; Meili Liu; Lisha Zheng; Yubo Fan (Pflügers Archiv - European Journal of Physiology, 2013)

Beraprost sodium attenuates cigarette smoke extract-induced apoptosis in vascular endothelial cells - Yan Chen; Hong Luo; Naixin Kang; Chaxiang Guan; Yingjiao Long; Jun Cao; Qin Shen; Junli Li; Min Yang; Hong Peng; Ping Chen (Molecular Biology Reports, 2012)

Gas Leakage Prediction Model of Large-Scale Explosions in Hard Rock Based on Quantification Theory - Xin-Zheng Wang; Jian-Jie Chen; Ping Li; Xiao She; Guan-Yi Niu (Transport in Porous Media, 2012)

Synthesis and studies on antidepressant activity of 2′,4′,6′-trihydroxychalcone derivatives - Xin Sui; Ying-Chun Quan; Yue Chang; Rui-Peng Zhang; Yin-Feng Xu; Li-Ping Guan (Medicinal Chemistry Research, 2012)

Human anti-EGFL7 recombinant full-length antibodies selected from a mammalian cell-based antibody display library - Feng Li; Yan-Hong Liu; Yan-Wen Li; Qian Ju; Lin Chen; Ping-Li Xie; Yue-Hui Li; Guan-Cheng Li (Molecular and Cellular Biochemistry, 2012)

Co-expression and Synergism Analysis of Vip3Aa29 and Cyt2Aa3 Insecticidal Proteins from Bacillus thuringiensis - Xiumei Yu; Tao Liu; Zhiguang Sun; Peng Guan; Jun Zhu; Shiquan Wang; Shuangcheng Li; Qiming Deng; Lingxia Wang; Aiping Zheng; Ping Li (Current Microbiology, 2012)

Phylogenic analysis of Chinese Leishmania isolates based on small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA) - Wang Guan; De-Ping Cao; Ke sun; Jia-nan Xu; Jun-rong Zhang; Da-Li Chen; Jian-Ping Chen (Acta Parasitologica, 2012)
The leishmaniases are zoonotic diseases caused by protozoan parasites of the genus Leishmania. Leishmaniases are still endemic in China, especially in the west and northwest froniter regions. To revalue the preliminary phylogenetic results of Chinese Leishmania isolates, we amplified partial fragment of small subunit ribosomal RNA (SSU rRNA) and 7 spliced leader RNA (7SL RNA), then tested the phylogenetic relationships among Chinese Leishmania isolates and their relatives by analyzing SSU rRNA gene sequences and 7SL RNA gene sequences. 19 SSU RNA sequences and 9 7SL RNA sequences were obtained in our study, then analyzed with 42 SSU RNA sequences and 32 7SL RNA sequences retrieved from Genbank, respectively. In the Bayesian analysis of the SSU RNA gene, the isolate MHOM/CN/93/GS7 and the isolate IPHL/CN/77/XJ771 are members of Leishmania donovani complex, while the isolate MHOM/CN/84/JS1 clustered with Leishmania tropica. The other 11 Chinese Leishmania isolates (MHOM/CN/90/WC, MCAN/CN/90/SC11, MHOM/CN/80/XJ801, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/ 89/GS5) form an unclassified group, defined as Leishmania sp., and the most relative species to this group is L. tarentolae. In the Bayesian analysis of the 7SL RNA gene, 9 Chinese Leishmania isolates also formed an unclassified group with L. tarentolae, including canine isolate 10, MHOM/CN/85/GS4, MHOM/CN/84/SD1, MCAN/CN/86/SC7, MHOM/CN/54/#3, MHOM/ CN/83/GS2, MHOM/CN/90/SC10H2, MHOM/CN/89/GS6 and MHOM/CN/89/GS5. We concluded that: (1) Chinese Leishmania isolates are non-monophyly group; (2) an unclassified group may exist in China, and the most relative species to this group is L. tarentolae; (3) MHOM/CN/84/JS1, which was previously assigned as L. donovani, was most genetically related to L. tropica strain MHOM/SU/74/K27.

Rapid determination of melamine in milk using water-soluble CdTe quantum dots as fluorescence probes - Minwei Zhang†; Hong Ping†; Xianyi Cao; Hongkun Li; Fengrui Guan; Chunyan Sun; Jingbo Liu (Food Additives & Contaminants: Part A, 2011)

Phenotypic and molecular characterization of rhizobacterium Burkholderia sp. strain R456 antagonistic to Rhizoctonia solani, sheath blight of rice - Bin Li; Bao-Ping Liu; Rong-Rong Yu; Miao-Miao Lou; Yan-Li Wang; Guan-Lin Xie; Hong-Ye Li; Guo-Chang Sun (World Journal of Microbiology and Biotechnology, 2011)

17β-Estradiol Protects Dopaminergic Neurons in Organotypic Slice of Mesencephalon by MAPK-Mediated Activation of Anti-apoptosis Gene BCL2 - Shuyan Wang; Ping Ren; Xiaobo Li; Yunqian Guan; Yu Alex Zhang (Journal of Molecular Neuroscience, 2011)

Human amniotic fluid-derived stem cells can differentiate into hepatocyte-like cells in vitro and in vivo - Hui Liu; Da-qing Liu; Bao-wei Li; Li-dong Guan; Zhi-feng Yan; Ya-li Li; Xue-tao Pei; Wen Yue; Min Wang; Yan-ping Lu; Hong-mei Peng; Yang Lv (In Vitro Cellular & Developmental Biology - Animal, 2011)

N-palmitoylethanolamide derivatives: synthesis and studies on anticonvulsant and antidepressant activities - Li-Ping Guan; Xin Sui; Xian-Qing Deng; Dong-Hai Zhao; You-Le Qu; Zhe-Shan Quan (Medicinal Chemistry Research, 2011)

Glycomyces halotolerans sp. nov., a novel actinomycete isolated from a hypersaline habitat in Xinjiang, China - Tong-Wei Guan; Zhan-Feng Xia; Jing Xiao; Nan Wu; Zheng-Jun Chen; Li-Li Zhang; Xiao-Ping Zhang (Antonie van Leeuwenhoek, 2011)

Saccharopolyspora lacisalsi sp. nov., a novel halophilic actinomycete isolated from a salt lake in Xinjiang, China - Tong-Wei Guan; Nan Wu; Zhan-Feng Xia; Ji-Sheng Ruan; Xiao-Ping Zhang; Ying Huang; Li-Li Zhang (Extremophiles, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Actinopolyspora xinjiangensis sp. nov., a novel exteremely halophilic actinomycete isolated from a salt lake in Xinjiang, China - Tong-Wei Guan; Ying Liu; Ke Zhao; Zhan-Fen Xia; Xiao-Ping Zhang; Li-Li Zhang (Antonie van Leeuwenhoek, 2010)

Synthesis and evaluation of antiinflammatory activity of substituted chalcone derivatives - Xue-Wu Zhang; Dong-Hai Zhao; Ying-Chun Quan; Liang-Peng Sun; Xiu-Mei Yin; Li-Ping Guan (Medicinal Chemistry Research, 2010)

Enhanced salt tolerance of transgenic poplar plants expressing a manganese superoxide dismutase from Tamarix androssowii - Yu Cheng Wang; Guan Zheng Qu; Hong Yan Li; Ying Jie Wu; Chao Wang; Gui Feng Liu; Chuan Ping Yang (Molecular Biology Reports, 2010)

A new screening method based on yeast-expressed human dipeptidyl peptidase IV and discovery of novel inhibitors - Chen-Xi Hu; Hui Huang; Li Zhang; You Huang; Zhu-Fang Shen; Ke-Di Cheng; Guan-Hua Du; Ping Zhu (Biotechnology Letters, 2009)

A new arylbenzofuran from the aerial parts of alfalfa - Shengchao Wang; Guogang Zhang; Jin Guan; Linxia Zhu; Lijuan Chen; Chunyuan Pan; Ping Li; Li Li (Journal of Natural Medicines, 2009)

FtsY Affects Sporulation and Antibiotic Production by whiH in Streptomyces coelicolor - Xue-Ling Shen; Hui-Jun Dong; Xiao-Ping Hou; Wen-Jun Guan; Yong-Quan Li (Current Microbiology, 2008)

Streptomyces nanningensis sp. nov. a novel Streptomycete from forest soil - Yi Jiang; Wen-Jun Li; Ping Xu; Ming-Gang Li; Meng-Liang Wen; Guan-Hua Du; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2005)

Monoclonal anti-androgen receptor antibodies: Production, characterization, and potential diagnostic applications - Charles C.-Y. Smith; Win-Jing Young; Chi-Huei Wang; Li-Ping Jin; Xiang-Dong Ji; Qi Guan; Min Wang; Chawnshang Chang (Molecular and Cellular Biochemistry, 1999)